Muscular hemangioma - Galarraga, José; Cassinelli, Daniel; Varela Soto, Ruben (Cirugía del Uruguay, 1977)
An 18-year-old girl presented muscular hemangioma which was hard to diagnose. Conservative surgery was performed and post-operatory evolution was excellent.